2003
DOI: 10.1002/cne.10793
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic domains of nociceptive‐responsive parabrachial neurons match terminal fields of lamina I neurons in the rat

Abstract: This study investigates, in the anesthetized rat, the dendritic extent of parabrachial (PB) neurons whose nociceptive response to noxious stimuli has been previously recorded with an extracellular micropipette. The PB neurons were then injected with biocytin through the recording micropipette, via a juxtacellular technique. The dendritic arborization of individual PB neurons was carefully compared with the projections of medullary (trigeminal) and spinal lamina I neurons. The latter projections were labeled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
3
15
0
Order By: Relevance
“…Nine out of a total of 32 labeled neurons were tested for antidromic activation from the amygdala, and two-both located in the peripheral part of the PBel-met the antidromic criteria. The results of the study by Bourgeais et al (2003) are thus congruent with the present demonstration of a few noxiously activated amygdala-projecting neurons in the very peripheral part of the PBel.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nine out of a total of 32 labeled neurons were tested for antidromic activation from the amygdala, and two-both located in the peripheral part of the PBel-met the antidromic criteria. The results of the study by Bourgeais et al (2003) are thus congruent with the present demonstration of a few noxiously activated amygdala-projecting neurons in the very peripheral part of the PBel.…”
Section: Discussionsupporting
confidence: 88%
“…In a recent study, Bourgeais et al (2003), using juxtacellular labeling of physiologically characterized neurons, specifically addressed how the location of cell bodies and the dendritic domains of nociceptiveresponsive neurons in the caudolateral part of the parabrachial nucleus related to the spinal and trigeminal afferent input. Neurons with receptive fields on the limbs had their dendritic arborizations within the lateral part of the PBel, the PBlc, PBdl, and PBcl, corresponding to the terminal field of ascending superficial dorsal horn fibers (Slugg and Light, 1994;Bernard et al, 1995;Feil and Herbert, 1995;Bourgeais et al, 2003). In almost all cases the cell body was located at the border between PBel and PBlc or in the subadjacent part of the outer PBel.…”
Section: Discussionmentioning
confidence: 99%
“…Nociceptive afferents that terminate in lPB and KF are known to ascend to dl-pons along the vsc (Slugg and Light, 1994;Bourgeais et al, 2003). In the present study, we found that many type II dendrites extended laterally into vsc, in which the distal dendritic processes also exhibited considerably higher number of varicosities.…”
Section: Pneumotaxic Neurons Integrate Pain And/or Musculoskeletal Insupporting
confidence: 60%
“…The somata and/or dendritic domains of some pneumotaxic neurons we identified were located in the lPB and KF nuclei, which are the terminating fields of some nociceptive afferents (Slugg and Light, 1994;Bourgeais et al, 2003). Recently, it was reported that certain respiratory rhythmic neurons in KF responded to cutaneous noxious stimuli and that the resulting respiratory enhancement was attenuated by bilateral inhibition of the parabrachial complex (Jiang et al, 2004).…”
Section: Pneumotaxic Neurons Integrate Pain And/or Musculoskeletal Inmentioning
confidence: 74%
“…However, the trigeminal nociceptive endings (Hayashi and Tabata 1990) stimulated by orofacial pain (Allen et al 1996) including trauma terminate chiefly in the caudal portion of the parabrachial (PB) external medial, external lateral, and Kölliker-Fuse subnuclei (Bourgeais et al 2003). During the last 15 years, evidence has accumulated indicating that significant nociceptive information in the spinal and trigeminal nuclei might be projected onto the amygdala and hypothalamus via the PB area of the rostral pons.…”
Section: Introductionmentioning
confidence: 99%